PENGARUH PEMAHAMAN MATA PELAJARAN MUATAN LOKAL BAHASA BANJAR TERHADAP HASIL BELAJAR SISWA KELAS V SDN 1 SYAMSUDIN NOOR KOTA BANJARBARU - Shebrina Zulfa; Nurul Huda Fitriani; Insaniyah; M. Ihsan Ramadhani (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The purpose of this study is to examine the influence of students’ understanding of the local content subject of Banjar Language on the learning outcomes of fifth grade students at SDN 1 Syamsudin Noor Banjarbaru City. Students’ understanding of the Banjar language is developed through both written and oral instruction delivered by teachers using the *Budaya dan Bahasa Banjar* module as the primary learning material to meet the predetermined assessment standards. This study employs a quantitative research approach in which the findings are analyzed using statistical data. The object of the study is the influence of understanding and learning outcomes in Banjar Language among fifth grade students at SDN 1 Syamsudin Noor. The research subjects consist of all fifth grade students totaling 53 students. The sample was selected using simple random sampling with 35 students chosen randomly. The research instrument was tested for validity and reliability using Microsoft Excel 2010 and SPSS 29 for Windows. Data were collected using a questionnaire. The data analysis technique used was the t-test. The results of data analysis indicate that the linear equation shows X (understanding) at 0.981 and Y (Banjar Language learning outcomes) at 25.485 indicating a strong influence of variable X on variable Y in achieving learning outcomes. Furthermore the t-test results show that t calculated = 73.80 and t table at a significance level of 5% = 0.334 with N = 35. Since t calculated (73.80) is greater than t table (0.334) the alternative hypothesis is accepted. It can be concluded that there is a significant influence of students’ understanding of the local content subject of Banjar Language on the learning outcomes of fifth grade students at SDN 1 Syamsudin Noor Banjarbaru City.